A fixed combination of cinnarizine/dimenhydrinate for the treatment of patients with acute vertigo due to vestibular disorders : a randomized, reference-controlled clinical study - Hahn, Ales; Sejna, Ivan; Stefflova, Bohdana; Schwarz, Mario; Baumann, Wolfgang (Clinical drug investigation, 2008)
BACKGROUND AND OBJECTIVE: Vestibular dysfunction commonly leads to - often severe - vertigo symptoms. The objective of this study was to compare the antivertiginous efficacy and tolerability of a fixed combination of cinnarizine/dimenhydrinate with those of betahistine in patients with acute vertigo due to vestibular disorders. METHODS: Sixty-six patients experiencing acute vertigo attacks participated in this prospective, double-blind, three-centre, comparative study. Patients who assessed at least one vertigo symptom as being of medium intensity (> or =2) on a 5-point visual analogue scale (VAS; from 0 = no symptoms to 4 = very severe symptoms) were randomly allocated to treatment with the fixed combination of cinnarizine 20 mg and dimenhydrinate 40 mg three times daily or betahistine 12 mg three times daily for 4 weeks. The primary efficacy endpoint was change in mean vertigo score, as determined by patients' assessments of 12 individual vertigo symptoms on the 5-point VAS after 4 weeks of treatment. RESULTS: Treatment with the fixed combination led to significantly greater improvements in mean vertigo scores than the reference therapy betahistine after 4 weeks of therapy (p = 0.013). The differences were clinically relevant, based on the Mann-Whitney estimator. Furthermore, the incidence of vertigo-associated vegetative symptoms was significantly reduced after 1 (p = 0.004) and 4 weeks (p = 0.023) in the fixed-combination group relative to the betahistine group. Three patients, all of them in the betahistine group, reported adverse events, none of which was considered serious. Almost all patients (n = 62) rated the tolerabilities of both medications as very good or good. CONCLUSION: The fixed combination of cinnarizine/dimenhydrinate was shown to be an effective and very well tolerated treatment option for patients with acute vertigo due to vestibular disorders. The combination proved to be significantly more efficient in reducing vertigo and associated vegetative symptoms than betahistine in such patients.
Keywords: Vertigo; lidé; Middle Aged; výsledek terapie; Adult; Tablets; Female; tablety; fixní kombinace léků; Drug Combinations; dimenhydrinát; cinarizin; akutní nemoc; Humans; vertigo; Dimenhydrinate; Double-Blind Method; lidé středního věku; mužské pohlaví; Periodicity; periodicita; Cinnarizine; Time Factors; ženské pohlaví; Acute Disease; Treatment Outcome; časové faktory; Male; Aged; dvojitá slepá metoda; dospělí; Vestibular Diseases; vestibulární nemoci; senioři